The Comparison of Main Characters and Social Beliefs Between Thai Legend “Mae Nak Phra Khanong” and Chinese Legend “Madame White Snake” - Phukwanpong, Pancheewa (Journal of Cultural Approach, 2015)
The Thai legend “Mae-NakPhraKhanong”, which means: “Lady Nak of PhraKhanong” and The Chinese legend “Madame White Snake” are well-known as traditional legends. They are similar in story plots, main characters, and social beliefs. Therefore, the purpose of this paper is to compare and to summarize these two legends in the following issues; (1) The main characters between “Mae-Nak” and “BaiSuzhen”, “Po-mak” and “Xu Xian”, “SomdetBudhacariya (TohBrahmaransi)” and “Fahai” (2) social beliefs especially ghost and devil stories from these traditional legends. This article will offer benefits to Thai academics who conduct research related to this topic in the future.